Antigen-Capturing Mesoporous Silica Nanoparticles Enhance the Radiation-Induced Abscopal Effect in Murine Hepatocellular Carcinoma Hepa1-6 Models - Kyungmi Yang; Changhoon Choi; Hayeong Cho; Won-Gyun Ahn; Shin-Yeong Kim; Sung-Won Shin; Yeeun Kim; Taekyu Jang; Nohyun Lee; Hee Chul Park (MDPI AG, 2021)
Immunomodulation by radiotherapy (RT) is an emerging strategy for improving cancer immunotherapy. Nanomaterials have been employed as innovative tools for cancer therapy. This study aimed to investigate whether mesoporous silica nanoparticles (MSNs) enhance RT-mediated local tumor control and the abscopal effect by stimulating anti-cancer immunity. Hepa1-6 murine hepatocellular carcinoma syngeneic models and immunophenotyping with flow cytometry were used to evaluate the immune responses. When mice harboring bilateral tumors received 8 Gy of X-rays on a single tumor, the direct injection of MSNs into irradiated tumors enhanced the growth inhibition of irradiated and unirradiated contralateral tumors. MSNs enhanced RT-induced tumor infiltration of cytotoxic T cells on both sides and suppressed RT-enhanced infiltration of regulatory T cells. The administration of MSNs pre-incubated with irradiated cell-conditioned medium enhanced the anti-tumor effect of anti-PD1 compared to the as-synthesized MSNs. Intracellular uptake of MSNs activated JAWS II dendritic cells (DCs), which were consistently observed in DCs in tumor-draining lymph nodes (TDLNs). Our findings suggest that MSNs may capture tumor antigens released after RT, which is followed by DC maturation in TDLNs and infiltration of cytotoxic T cells in tumors, thereby leading to systemic tumor regression. Our results suggest that MSNs can be applied as an adjuvant for in situ cancer vaccines with RT.